Is cerclage height associated with preterm delivery in women undergoing ultrasound-indicated cervical cerclage?. (18th April 2012) - Chatfield, S; Cook, JR; Chandiramani, M; Sykes, L; Simcox, R; Abbott, D; Jones, B; Loudon, J; Shennan, AH; Bennett, PB; Terzidou, V
Abstract : Objective: To determine whether the level of an ultrasound (USS) indicated cervical cerclage is a factor in the subsequent risk of preterm delivery. Study Design and Results: A retrospective cohort study of women with a singleton pregnancy undergoing USS-indicated cerclage in two UK tertiary referral centres between 2001–2011. Demographic data, cervical dimensions (length, suture distance from external/internal os) and obstetric outcomes were obtained. In 131 women undergoing USS-indicated cerclage, the preterm birth rate at <34 and <37 weeks gestation was 28% and 41% respectively. The cohort was divided according to cerclage height from the external os or suture height as percentage of total cervical length, at first USS after suture insertion and the RR of preterm delivery at 34 and 37 weeks calculated (Table 1). Conclusion: It has been thought, historically, that the closer a cervical cerclage is to the internal os the more effective it will be, but this has never been proven. This is the largest reported cohort of USS-indicated cervical cerclage and shows that the higher a cervical cerclage is placed the lower the subsequent risk of preterm delivery. When placing a cervical cerclage every effort should be made to place it as high as possible.